Risk Factors for Hydrocephalus in Neonatal Purulent Meningitis: A Single-Center Retrospective Analysis. (May 2021) - Chen, Bin; Zhai, Qian; Ooi, Kokwin; Cao, Yun; Qiao, Zhongwei
Objective: Hydrocephalus is a potentially lethal complication of neonatal purulent meningitis. Early detection of hydrocephalus helps to determine optimal treatment, improve prognosis, and reduce financial burden. We aimed to analyze the risk factors for hydrocephalus in neonates with purulent meningitis and discuss the characteristics of the disease. Methods: The records of neonatal purulent meningitis admitted to the Children Hospital of Fudan University from January 2013 to September 2019 were retrospectively included in the study cohort. The data of clinical, laboratory, and cranial magnetic resonance images (MRIs) were collected and analyzed (except discharge data) by univariate analysis, and P values <.05 were further analyzed by multivariate logistic regression. Results: A total of 197 children who met the inclusion criteria were enrolled in the study cohort. Overall, 39.6% (78/197) of the patients had positive pathogen cultures, and 60.4% (119/197) of patients had clinical diagnosis of meningitis with negative pathogen cultures. Among 197 children, 67 of them experienced hydrocephalus, and the factors that were significantly associated with hydrocephalus in multivariate analysis were female sex, cerebrospinal fluid glucose <2 mmol/L, periventricular leukomalacia, punctate white matter lesions, and pyogenic intraventricular empyema. Children with hydrocephalus had a lower cure rate of meningitis (31.3% vs 75.4%), and poor discharge outcomes. In addition, they had longer length of hospital stay and higher hospital cost. Conclusions: Female sex, cerebrospinal fluid glucose <2 mmol/L, periventricular leukomalacia, punctate white matter lesions, and pyogenic intraventricular empyema were identified as risk factors for hydrocephalus in neonatal purulent meningitis. Children with hydrocephalus had poor discharge outcomes and increased financial burden on their families.